TRANSAKSI UANG ELEKTRONIK E-MARTABE DITINJAU DARI FIQH MUAMALAH PADA BANK SYARIAH - Yusuf Yusuf; Sri Sudiarti; Muhammad Ikhsan Harahap (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
E-Martabe Sharia Electronic Money is a product of Bank Sumatera Utara which is made based on co-branding with Bank Mandiri and to support GNNT. This study aims to see the suitability of E-Martabe Bank Sumut KCP Syariah Simpang Kayu Besar products based on fiqh muamalah with DSN-MUI fatwa No. 116 / DSN-MUI / IX / 2017 concerning Sharia Electronic Money. The method used in this study is a descriptive qualitative approach whose data collection techniques use interview, observation, and documentation techniques. This research shows that this E-Martabe product is not fully in accordance with sharia principles as seen from the muamalah fiqh and DSN-MUI fatwa No. 116 / DSN-MUI / IX / 2017 concerning Sharia Electronic Money.